Antibacterial and antifungal activity of the starfish Oreaster reticulatus (Valvatida: Oreasteridae) and the sea urchins Mellita quinquiesperforata (Clypeasteroida: Mellitidae) and Diadema antillarum (Diadematoida: Diadematidae) from the Colombi - Pastrana Franco, Orlando (2015)
As benthic organisms, sea stars and sea urchins are constantly exposed to a large number of bacteria, fungi and viruses, some of them potentially harmful. To survive, these echinoderms depend on their immune system, which has developed a number of compounds which act as antimicrobial defense strategies. In this work, the antibacterial and antifungal activities of the extracts of the starfish Oreaster reticulatus and sea urchins Diadema antillarum and Mellita quinquiesperforata collected in the Caribbean Cordobés were evaluated against the bacteria Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae and against the phytopathogenic fungi Fusarium sp., Scleortium sp., and Rhizoctonia sp. Our results show that O. reticulatus and D. antillarum produce compounds producing bacterial inhibition at low concentrations (< 100 μg / ml), while, M. quinquiesperforata extracts showed no inhibition at any of the concentrations tested. Specifically, the strain of S. aureus was the one with greater susceptibility to the extracts evaluated, i.e. the metabolites produced by echinoderms inhibit more easily gram + bacteria. Only the D. antillarum dichloromethane affected Fusarium sp. with inhibition of 78.2 % and 56.5 % at concentrations of 2 000 and 100 μg / ml. Strains of the fungi Sclerotium sp. and Rhizoctonia sp. had resistance to all extracts.